Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.3390/app11041457
|View full text |Cite
|
Sign up to set email alerts
|

Typology Selection of Retaining Walls Based on Multicriteria Decision-Making Methods

Abstract: In civil engineering and construction, in the selection of the most adequate and sustainable alternative, all of the alternatives and selection criteria, such as the requirements of the construction process (which are often overlooked) and the preferences of designers, clients, or contractors, are not always taken into account. The purpose of this article is to suggest a methodology that may allow studying all of the possible alternatives to find the most ideal solution among all of the existing possibilities … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 39 publications
0
10
0
1
Order By: Relevance
“…Retaining systems can be classified according to several different criteria: construction method (fill or cut systems), load support mechanism (externally or internally stabilized systems), system stiffness (rigid or flexible systems), stability mechanism, applications, and lifespan (permanent or temporary systems) [1]. Based on load support mechanism, O' Rourke and Jones classified the retaining systems into three main categories: Internally Stabilized Systems (ISS), Externally Stabilized Systems (ESS), and Hybrid Systems (HS) [2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Retaining systems can be classified according to several different criteria: construction method (fill or cut systems), load support mechanism (externally or internally stabilized systems), system stiffness (rigid or flexible systems), stability mechanism, applications, and lifespan (permanent or temporary systems) [1]. Based on load support mechanism, O' Rourke and Jones classified the retaining systems into three main categories: Internally Stabilized Systems (ISS), Externally Stabilized Systems (ESS), and Hybrid Systems (HS) [2].…”
Section: Introductionmentioning
confidence: 99%
“…Clough and O'Rourke [21] suggested profiles of lateral wall deformation and the ground surface movement behind it due to excavation activities, as illustrated in Fig. (1). During the initial stages of excavation and before installing the lateral supports, the wall will be deformed as a cantilever, as shown in Fig.…”
Section: Introductionmentioning
confidence: 99%
“…They concluded that the use of computational methods minimizes uncertainties arising from limited number of soil properties. Muñoz-Medina et al [28] searched for a suitable methodology for the selection of retaining walls for different infrastructures and environments.…”
Section: Introductionmentioning
confidence: 99%
“…Mesmo que exista uma investigação geotécnica subsequente ao início das concepções de projeto, a incerteza é algo inevitável em projetos com solos e rochas, fazendo com que o profissional defina algumas características pré-projeto que raramente condizem com as condições atuais do terreno [9]. No que tange à escolha de contenções existem alguns métodos e critérios já avaliados na literatura científica em diversos países como Espanha [10], Reino Unido [11] e Malásia [12]. Os métodos avaliam indicadores de impacto ambiental, ciclo de custos, impacto social e populacional que, por vezes, são medidas pertinentes apenas ao próprio contexto da pesquisa em que são aplicados e avaliados somente após o término da obra, não avaliando fatores incluídos em premissas adotadas na fase de concepção do projeto geotécnico.…”
Section: Introductionunclassified